CAPES and its condition as a regulatory agency for post-graduate education in Brazil - Addor, Nicolas; Costódio, Marcos Viana (Revista Videre, 2020)
The research intends to analyze the legal and administrative structure of the Coordination of Improvement of Higher-Level Personnel - CAPES and its relevance to the regulation of the stricto sensu Brazilian postgraduate course, in order to demonstrate that the entity has, in fact, the condition of regulatory agency. For this, it is necessary to address three points using deductive methodology with bibliographic and documentary sources related to CAPES: The first point seeks to describe and contextualize the formation of the CAPES foundation, as well as to report the administrative activities that it exerts on the post-graduation. In the second point, it addresses the historical process of the emergence of regulatory agencies, also analyzing the objectives and attributions assigned to them. Finally, in the third point, a critical analysis was made of the condition of CAPES as a regulatory agency. In this way, it is understood that a public foundation, when it serves a typical function of the State, is not, despite what formally the law that instituted it, a foundation, but rather, an autarchy, which makes it possible to compare it, with a regulatory agency. It concludes, therefore, that because of the extensive powers that CAPES exercises over postgraduate programs, its autarkic nature and regulating an economic activity in a broad sense, it is considered that it is in reality a regulatory agency for post- graduation. Moreover, given the terminological emptying of the notion of agency, the differentiated condition of the managers is not a relevant factor for the categorization of a body of indirect administration as an agency.